Efficacy of a new generation intracoronary optical coherence tomography imaging system with fast pullback. Issue 3 (5th February 2023) - Nishi, Takeshi; Kume, Teruyoshi; Yamada, Ryotaro; Koto, Satsohi; Sasahira, Yoshitaka; Okamoto, Hiroshi; Tamada, Tomoko; Koyama, Terumasa; Imai, Koichiro; Neishi, Yoji; Ughi, Giovanni J.; Uemura, Shiro
Abstract: Objectives: We sought to investigate whether a novel, fast‐pullback, high‐frequency optical coherence tomography (HF‐OCT) imaging system enables data acquisition with a reduced amount of contrast agents while retaining the same qualitative and quantitative lesion assessment to conventional OCT. Background: The increased amount of administered contrast agents is a major concern when performing intracoronary OCT. Methods: The present study is a single‐center, prospective, observational study including 10 patients with stable coronary artery disease. A total of 28 individual coronary arteries were assessed by both fast‐pullback HF‐OCT and by conventional OCT. Results: The contrast volume used in each OCT run for the HF‐OCT system was significantly lower than for the conventional OCT system (5.0 ± 0.0 mL vs. 7.8 ± 0.7 mL, respectively, with a mean difference of −2.84 [95% confidence interval [CI]: −3.10 to −2.58]). No significant difference was found in the median value of the clear image length between the two OCT systems (74 mm [interquartile range [IQR]; 63, 81], 74 mm [IQR; 71, 75], p = 0.89). Fast‐pullback HF‐OCT showed comparable measurements to conventional OCT, including minimum lumen area (3.27 ± 1.53 mm 2 vs. 3.21 ± 1.53 mm 2, p = 0.27), proximal reference area (7.03 ± 2.28 mm 2 vs. 7.03 ± 2.34 mm 2, p = 0.96), and distal reference area (5.93 ± 1.96 mm 2 vs. 6.03 ± 2.02 mm 2, p = 0.23). Qualitative OCT findings were comparable between the fast‐pullback HF‐OCT runs and conventional OCT with respect to identifying lipid‐rich plaques, calcifications, layered plaques, macrophages, and cholesterol crystals. Conclusion: With the fast pullback function of a novel HF‐OCT imaging system, we acquired OCT images using a significantly lower amount of contrast volume while retaining a comparable qualitative and quantitative lesion assessment to conventional OCT.